Model Pembelajaran Agama Hindu Pada Pendidikan Anak Usia Dini - Wiasti, Ni Komang (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2024)
The objective of this study is to examine a Hindu religious learning model that can be applied in Early Childhood Education. The effectiveness of the Hindu religious education process hinges on the instructor or educator's ability to master the content and create a well-structured and integrated system. The learning model consists of multiple interconnected aspects or components, facilitating the dissemination of information or content. This study employs a qualitative descriptive approach to gather data through the means of observation, interviews, and documentation. The acquired data is subsequently subjected to reduction, verification, and conclusion drawing. The learning models that can facilitate the Hindu religious learning process in early infancy include: (1) Group learning model; (2) Angular Learning Model; (3) Regional Learning Model; (4) Learning Center Model. These four educational methods have the potential to enhance the fine motor skills of young children.